Pengaruh Budaya Organisasi, Lingkungan Kerja dan Kompetensi Terhadap Kinerja Pegawai: Studi Empiris pada PT. PLN Nusa Daya Site FBB Labuanbajo, Nusa Tenggara Timur - Nur Muchlis Wijaya; Imaculata Fatima; Hyronimus Se (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of organizational culture, work environment, and competence on employee performance at PT. PLN Nusa Daya Site FBB Labuanbajo. The population and sample of this study were all 50 employees. The sampling technique used saturated sampling and was analyzed using SPSS. The results of this study indicate that organizational culture has a positive and significant effect of 0.112, the work environment has a positive and significant effect of 0.138, and competence has a positive and significant effect of 0.344, so it can be concluded that the first, second, and third hypotheses can be accepted.